2023
DOI: 10.3390/w15224020
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Future-Integrated Urban Water Management Using a Risk and Decision Analysis Framework: A Case Study in Denver–Colorado Metro Area (DCMA)

Bowen He,
Han Zheng,
Qun Guan

Abstract: This study examines the DCMA concerning the future risk of the water security status. We considered three risk factors: population growth, economic growth, and natural water supply–demand differences. In the risk analysis part, we consulted with experts from several sectors including academia, Non-Governmental Organizations (NGOs), and industry, to predict that the probability of future water stresses in high-, medium-, and low-risk scenarios are 0.73, 0.24, and 0.03, respectively. In the decision analysis par… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 19 publications
0
1
0
Order By: Relevance
“…Climate change has become a severe problem for the modern world. Extensive studies have found that climate change can influence every aspect of society, from community vulnerability and resilience [1][2][3][4] to fresh water and climate ecosystems [5][6][7][8][9]. To address the climate crisis, electric vehicles (EVs) have been adopted worldwide to help fight climate change by reducing emissions compared to conventional gasoline vehicles (CVs) [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…Climate change has become a severe problem for the modern world. Extensive studies have found that climate change can influence every aspect of society, from community vulnerability and resilience [1][2][3][4] to fresh water and climate ecosystems [5][6][7][8][9]. To address the climate crisis, electric vehicles (EVs) have been adopted worldwide to help fight climate change by reducing emissions compared to conventional gasoline vehicles (CVs) [7,10].…”
Section: Introductionmentioning
confidence: 99%
“…The advantage of the composite index model is that it provides a quantitative method to quantify an abstract modeling concept, such as WEF nexus security, so that further research can be implemented, such as comparing WEF nexus security between countries. Thus, it has been widely adopted to evaluate a community's social vulnerability and social fabric associated with natural hazards' mitigation evaluations (Cutter et al, 2003;Camp et al, 2023;He, 2023;He et al, 2023aHe et al, , 2023b. Additionally, the WEF index model is a critical concept that recognizes the interconnections and interdependencies among water, energy, and food systems to evaluate and manage these interlinkages.…”
Section: Introductionmentioning
confidence: 99%